Demokrasi dan Negara Hukum - Author: Muntoha (Fakultas Hukum Universitas Islam Indonesia, 2009)
The rule of law state shall be based on democracy. This because there is a correlation between a rule of law state which relies on a constitution and sovereignty of the people which is run by democracy. In democracy, public’s participation is a core essence. However, democracy withouta robust regulation will lose its direction, and similarly, law without democracy will lose its true meaning. As a result, in a democratic rule of law state, law is developed and enforced in accordance with the principle of democracy. Law must not be made, approved, interpreted, and enforced merely by power (machstaat), but rather this shall be regulated by law (rechstaat).Keywords: democracy, rule of law